Taught postgraduate air transport management degrees in the UK: A systematic review and analysis - Mayer, Robert; Budd, Lucy; Ison, Stephen (Elsevier, 2024)
This paper examines the provision, structure and curriculum content of taught postgraduate (Masters’ level) Air Transport Management degree programmes in the UK. In the academic year 2022–23, 14 UK Universities offered 19 different programmes. These programmes differed in terms of their duration, the fees that were charged, the delivery models, the content and the assessment regimes. In addition to examining the content and structure of the programmes, the paper conducts a SWOT analysis of the suite of degree programmes. While the inherent advantages of having a diversity of programmes for individuals, academic institutions and the air transport sector are recognised, it is suggested that prospective students and employers are cognisant of the differences between programmes to make informed decisions about their suitability and ability to meet personal career objectives and workplace planning requirements.